Coated electrodes with polymer binders for lithium-ion batteries
By mixing the particulate polymer adhesive composition with the electrode material, an efficient electrode slurry is solved, and the problem of insufficient adhesive viscosity and adhesion in electrode production is achieved, and better electrode performance is achieved.
Patent Information
- Application Number
- CN202080089466.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-23
- Filing Date
- 2020-11-23
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-11-23
AI Technical Summary
In the existing electrode production methods, the powder form of polymer adhesives has problems of high viscosity and insufficient adhesion, which affects the performance of the electrode.
Using a granular polymer binder composition, containing more than 90% of raspberry-shaped particles of 400 μm or larger but less than 2.5 mm, it is improved by dissolving it in a solvent and mixing it with the electrode material to form a slurry and coat the electrode substrate to improve the Adhesion.
The viscosity of the slurry is significantly reduced, the adhesion and peel strength of the electrode are enhanced, and the overall performance of the electrode is improved.
Smart Images

Figure CN114868208B_ABST
Abstract
Description
Field of the Invention
[0001] The present invention relates to polymer binder compositions for electrochemical device coatings. Background of the Invention
[0003] The electrodes are used in energy storage devices, including but not limited to batteries, capacitors, supercapacitors, non-aqueous secondary batteries, etc.
[0004] There are two main methods of electrode production: the "wet process" and the "dry process". In the wet process, a polymer binder in the form of a solvent solution or dispersion is mixed with one or more active powdered electrode-forming materials to form a slurry dispersion or paste. This dispersion or paste is then applied to one or both surfaces of a conductive substrate and dried to form a bonded composite electrode layer. The electrode layer can then be calendered. This process is demonstrated in US 5,776,637 and US 6,200,703, where the fluoropolymer binder is dissolved in NMP.
[0005] Surprisingly, it has now been found that by using the polymer binder composition in particulate form, better adhesion can be achieved in the final battery product. Advantageously, such slurries produced from agglomerated fluoropolymer compositions exhibit lower viscosity and provide better adhesion to the electrodes.
[0006] Other benefits include: better adhesive dispersion, resulting in reduced adhesive usage. Summary of the invention
[0007] The present invention relates to a method for making an improved battery electrode, comprising: providing a granular polymer binder composition such that greater than 90% by weight, preferably greater than 95% by weight, of the particles of the granular polymer binder composition are 400 μm or larger but less than 2.5 mm, preferably the granular binder composition has a raspberry morphology; mixing the granular binder, a solvent and an electrode material to form a slurry, wherein the granular polymer binder composition is dissolved in the solvent; and coating an electrode substrate with the resulting slurry. Preferably, the polymer binder composition comprises a fluoropolymer composition, preferably a polyvinylidene fluoride polymer composition, i.e., "PVDF". By using a granular polymer binder composition, the applicant has found that better dissolution of the polymer binder composition results in a viscosity reduction of at least 5% compared to the viscosity when the same binder is used in powder form, and an increase in the peel strength of the cathode. Electrodes made using the method of the present invention have better adhesion.
[0008] When the binder powder is subjected to compaction / granulation and then used in a process for making an electrode, the result unexpectedly reduces the slurry viscosity and improves the adhesion of the polymer binder composition to the electrode substrate compared to the case where the same binder is used without granulation (used in powder form).
[0009] Applicants have discovered a method for improving the adhesion of battery electrodes. The method comprises dissolving a particulate polymer binder composition (preferably comprising a fluoropolymer composition, preferably a polyvinylidene polymer composition) in a solvent to form a slurry, adding an electrode material to the slurry, and then coating the electrode substrate with the slurry containing the active material. The particulate polymer binder composition is characterized in that its apparent density is higher than 0.4, preferably higher than 0.6, and even more preferably higher than 0.8 g / cc, and wherein the particulate polymer binder consists of agglomerated particles having a raspberry morphology.
[0010] The present invention relates to a method for forming an energy storage device, comprising the following steps:
[0011] a) dissolving a particulate polymer binder (preferably a fluoropolymer composition) in a solvent to obtain a binder dispersion;
[0012] b) mixing the binder dispersion with an active powdered electrode-forming material to form a homogeneous blend, and
[0013] c) applying the homogeneous blend to at least one surface of a conductive substrate to form an electrode,
[0014] wherein greater than 90% of the particulate polymer binder particles are 400 μm or greater but less than 2.5 mm, preferably 400 to 2000 microns, and the bulk density of the polymer binder is greater than 0.4 g / cc, preferably greater than 0.6 g / cc, wherein the particles have a raspberry morphology. Particle size is measured by measuring the percentage passing through a sieve of each mesh size.
[0015] The present invention also relates to electrodes formed by this method having better adhesion than a binder formed from the same polymer binder in powder form.
[0016] Aspects of the Invention
[0017] Aspect 1: A method for producing a battery electrode, the method comprising the following steps:
[0018] a. providing a granular polymer binder composition, wherein the binder composition comprises agglomerated particles, the agglomerated particles preferably having a raspberry morphology, wherein greater than 95% by weight of the agglomerated particles are 400 μm or greater but less than 2.5 mm, and have a bulk density greater than 0.4 g / cc,
[0019] b. mixing a particulate polymer binder composition, a solvent and an electrode material to provide an electrode-forming composition, wherein the polymer binder composition is dissolved in the solvent,
[0020] c. applying an electrode-forming composition to at least one surface of a conductive substrate, and
[0021] d. Evaporating the organic solvent in the electrode-forming composition to form a composite electrode layer on the conductive substrate.
[0022] Aspect 2: The method according to aspect 1, wherein step (b) comprises:
[0023] b1. adding the granular polymer binder composition to an organic solvent,
[0024] b2. Mixing until dissolved to provide a solution of the granular binder,
[0025] b3. Mixing the electrode material and the solution of the particulate binder to provide an electrode-forming composition.
[0026] Aspect 3: A method as described in Aspect 1 or 2, wherein the granular polymer adhesive composition comprises a polymer selected from the following group: fluoropolymers, SBR, ethylene vinyl acetate (EVA), acrylic polymers, polyurethanes, styrenic polymers, polyamides, polyesters, polycarbonates and thermoplastic polyurethanes (TPU) and combinations thereof.
[0027] Aspect 4: The method of aspect 1 or 2, wherein the particulate polymer binder comprises a fluorine-containing polymer.
[0028] Aspect 5: The method of aspect 4, wherein the molten salt is dried at 450°F (232°C) and 100 seconds according to ASTM method D-3835. -1 The fluoropolymer has a melt viscosity greater than 5 kpoise, preferably greater than 15 kpoise, measured at 100 rpm.
[0029] Aspect 6: The method according to aspect 4, wherein the fluorine-containing polymer comprises a polyvinylidene fluoride polymer, which contains at least 50% by weight of vinylidene fluoride monomer units, preferably at least 75% by weight of vinylidene fluoride monomer units.
[0030] Aspect 7: The method according to aspect 4, wherein the fluorine-containing polymer is a copolymer comprising vinylidene fluoride monomer units and 1 to 30 wt % of hexafluoropropylene monomer units.
[0031] Aspect 8: The method as described in any one of Aspects 1 to 7, wherein the electrode material comprises an active material selected from the following group: oxides, sulfides or hydroxides of lithium and transition metals; carbon-containing materials; nano-titanates and combinations thereof.
[0032] Aspect 9: The method as described in Aspect 8, wherein the electrode material further includes an additive that imparts conductivity.
[0033] Aspect 10: The method according to any one of aspects 1 to 7, wherein the electrode material comprises a carbonaceous material in the form of particles having an average diameter of 0.5-100 μm.
[0034] Aspect 11: The method of any one of aspects 1 to 10, wherein the agglomerated particles have a bulk density of 0.6 g / cc or greater.
[0035] Aspect 12: The method of any one of aspects 1 to 11, wherein the agglomerated particles are larger than 400 microns but smaller than 2000 microns.
[0036] Aspect 13: An electrode formed by the method of any one of aspects 1 to 12.
[0037] Aspect 14: A battery comprising an electrode produced by the method of any one of aspects 1 to 12. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] FIG. 1 shows a fluoropolymer adhesive composition powder at a magnification of 70X.
[0039] FIG. 2 shows a fluoropolymer adhesive composition powder at a magnification of 20,000.
[0040] FIG. 3 shows a fluoropolymer adhesive composition powder at a magnification of 50,000.
[0041] FIG. 4 shows a granular fluoropolymer binder composition at a magnification of 70X.
[0042] FIG. 5 shows a granular fluoropolymer adhesive composition at a magnification of 10,000.
[0043] FIG6 shows a granular fluoropolymer adhesive composition at a magnification of 50,000. DETAILED DESCRIPTION OF THE INVENTION
[0045] As used herein, copolymer refers to any polymer having two or more different monomer units, and will include terpolymers as well as copolymers having more than three different monomer units.
[0046] As used herein, percentages are by weight unless otherwise indicated, and molecular weights are weight average molecular weight unless otherwise indicated.
[0047] References cited throughout this application are incorporated herein by reference.
[0048] A raspberry structure is a material where the particles consist of smaller primary particles that can be observed by microscopy. This structure / morphology is well known in the art.
[0049] For a given polymer composition, apparent density is a way to distinguish between powders and granules. Apparent density is the bulk density of a powder. It provides the mass of loose powder per unit volume. This value is a preliminary, low-cost assessment of a powder to determine batch-to-batch consistency. A low apparent density can be an indication of (smaller) fine granules, while a high apparent density can be an indication of large granules. In addition, if the powder is heavily agglomerated, this may manifest as an increase in apparent density. The bulk density or apparent density is measured by gently introducing a sample of known mass into a measuring cylinder and carefully leveling the powder without compacting it. The apparent untapped volume is then read to the nearest scale unit.
[0050] A powder is defined as a particle size of more than 90% by weight of the particles being less than 300 microns, preferably less than 200 microns.
[0051] The slurry viscosity is measured at 25°C using a Brookfield viscometer. A SSA7R chamber is used with a spindle number of 15. The solid content (%) of the slurry is in the range of 40 wt % to 87 wt %. The viscosity can be measured at a solid content of 71 wt % to 72 wt %.
[0052] The manner of carrying out the invention will now be generally described with respect to its specific preferred embodiment, namely a polyvinylidene fluoride based polymer prepared in aqueous emulsion polymerization. Although the invention has been generally described with respect to PVDF polymers, those skilled in the art will recognize that similar polymerization and application techniques can be used to prepare other polymer adhesive compositions.
[0053] The present invention provides a method for preparing a binder composition and a method for preparing an electrode comprising the binder composition. The method comprises dissolving a granular binder, wherein more than 90% by weight, preferably more than 95% by weight of the granular binder particles are 400 microns or larger but less than 2.5 mm, preferably 400 microns or larger to 2000 microns, and the apparent density is greater than 0.4 g / cc, preferably greater than 0.6 g / cc. The particle size is measured by measuring the weight percentage passing through a sieve of each mesh size.
[0054] It has surprisingly been found that the use of a particulate polymer binder composition results in lower slurry viscosity and increased adhesion of the slurry to the electrode substrate compared to the use of a powder form wherein greater than 90% by weight of the particles are smaller than 300 microns.
[0055] The fluoropolymer polymer binder composition is preferably a fluoropolymer composition which may be a homopolymer or a copolymer, with or without functional groups. PVDF is a preferred fluoropolymer.
[0056] Compacting / granulating polymers is well known in the art to reduce dust, control particle size, control bulk density or increase dissolution / dispersion rate. See, for example, https: / / www.fitzpatrick-mpt.com and the Fitzpatrick Company brochure "Roll Compaction RC-5 / 09" where granulation is discussed.
[0057] Fluoropolymers
[0058] The term fluoropolymer means any polymer having in its chain at least one monomer chosen from compounds containing a vinyl group capable of opening for polymerization and which contains at least one fluorine atom, at least one fluoroalkyl group or at least one fluoroalkoxy group directly attached to the vinyl group.
[0059] Useful fluoropolymers are thermoplastic homopolymers, and copolymers having more than 50% by weight of fluoromonomer units, preferably more than 65% by weight, more preferably more than 75% by weight, and most preferably more than 90% by weight of one or more fluoromonomers. Fluorine-containing monomers that can be used to form fluoropolymers include, but are not limited to: vinylidene fluoride (VDF or VF2), 1,2-difluoroethylene, trifluoroethylene (VF3); tetrafluoroethylene (TFE), trifluoroethylene (TrFE), chlorotrifluoroethylene (CTFE), hexafluoropropylene (HFP), vinyl fluoride (VF), hexafluoroisobutylene (HFIB), perfluorobutylethylene (PFBE), pentafluoropropylene, 3,3,3-trifluoro-1-propylene, 2-trifluoromethyl-3,3,3-trifluoropropylene, fluorinated (alkyl) ethylene ethers, including perfluoromethyl ether (PMVE), perfluoroethyl vinyl ether (PEVE), perfluoropropyl vinyl ether (PPVE), perfluorobutyl vinyl ether (PBVE), long chain perfluorovinyl ethers, fluorinated dioxoles, such as perfluoro(1,3-dioxole); perfluoro(2,2-dimethyl-1,3-dioxole) (PDD), C4 and higher partially fluorinated or perfluorinated alpha olefins, C3 and higher partially fluorinated or perfluorinated cyclic olefins, and combinations thereof.
[0060] The present invention is applicable to thermoplastic fluoropolymers, homopolymers and copolymers. Preferred polymer binders include, but are not limited to, homopolymers of polyvinylidene fluoride and copolymers of polyvinylidene fluoride and hexafluoropropylene (VDF-HFP).
[0061] Vinylidene fluoride polymers will be used to illustrate the present invention and are preferred polymers (including homopolymers and copolymers). Such copolymers include those containing at least 50% by weight, preferably at least 75% by weight, more preferably at least 80% by weight, and even more preferably at least 85% by weight of vinylidene fluoride copolymerized with one or more comonomers. Exemplary comonomers may be selected from the group consisting of tetrafluoroethylene, trifluoroethylene, chlorotrifluoroethylene, hexafluoropropylene, vinyl fluoride, pentafluoropropylene, tetrafluoropropylene, trifluoropropylene, perfluorovinyl ethers, such as perfluoroethyl vinyl ether and perfluoro-2-propoxypropyl vinyl ether, perfluoromethyl vinyl ether, perfluoropropyl vinyl ether and any other monomers that are easily copolymerized with vinylidene fluoride, one or more partially or fully fluorinated alpha-olefins, such as 3,3,3-trifluoro-1-propoxypropyl vinyl ether. The invention relates to a fluorinated monomeric monomer comprising a fluorinated olefin, 1,2,3,3,3-pentafluoropropylene, 3,3,3,4,4-pentafluoro-1-butene, a partially fluorinated olefin hexafluoroisobutylene, a fluorinated dioxole, such as perfluoro(1,3-dioxole) and perfluoro(2,2-dimethyl-1,3-dioxole), an allylic, partially fluorinated allylic, or fluorinated allylic monomer, such as 2-hydroxyethyl allyl ether or 3-allyloxypropylene glycol, and ethylene or propylene. Other monomeric units in these polymers may include any monomer containing a polymerizable C=C double bond. Additional monomers may be 2-hydroxyethyl allyl ether, 3-allyloxypropylene glycol, an allylic monomer, ethylene or propylene, acrylic acid, methacrylic acid.
[0062] In one embodiment, up to 30 wt%, preferably up to 25 wt%, more preferably up to 15 wt% of hexafluoropropylene (HFP) units and 70 wt% or more, preferably 75 wt% or more, more preferably 85 wt% or more of VDF units are present in the vinylidene fluoride polymer. It is desirable that the HFP units be distributed as evenly as possible, thereby providing a PVDF-HFP copolymer with excellent dimensional stability in the final use environment.
[0063] The most preferred copolymers and terpolymers of the present invention are those wherein the percentage of vinylidene fluoride units in the total weight of all monomer units in the polymer is greater than 50%, preferably at least 60% by weight, more preferably greater than 70% by weight of the total weight of units. Copolymers, terpolymers and higher polymers of vinylidene fluoride can be prepared by reacting vinylidene fluoride with one or more monomers selected from the group consisting of vinyl fluoride, trifluoroethylene, tetrafluoroethylene, partially or fully fluorinated α-olefins such as one or more of 3,3,3-trifluoro-1-propylene, 1,2,3,3,3-pentafluoropropylene, 3,3,3,4,4-pentafluoro-1-butene and hexafluoropropylene, partially fluorinated olefin hexafluoroisobutylene, perfluorinated vinyl ethers such as perfluoromethyl vinyl ether, perfluoroethyl vinyl ether, perfluoro-n-propyl vinyl ether and perfluoro-2-propoxypropyl vinyl ether, fluorinated dioxoles such as perfluoro(1,3-dioxole) and perfluoro(2,2-dimethyl-1,3-dioxole), allylic, partially fluorinated allylic or fluorinated,
[0064] Emulsification method
[0065] Fluoropolymers, such as polyvinylidene-based polymers, can be prepared by any method known in the art using aqueous free radical emulsion polymerization - although suspension, solution and supercritical CO2 polymerization methods can also be used. Methods such as emulsion polymerization and suspension polymerization are preferred and are described in US6187885 and EP0120524. Most preferred is emulsion polymerization.
[0066] In a general emulsion polymerization process, deionized water, a water-soluble surfactant capable of emulsifying the reaction materials during the polymerization process, and an optional paraffin antifouling agent are added to the reactor. The mixture is stirred and deoxygenated. A predetermined amount of chain transfer agent CTA is then introduced into the reactor, the reactor temperature is raised to the desired level, and monomers (e.g., vinylidene fluoride and possibly one or more comonomers) are fed into the reactor. Once the initial charge of monomers is introduced and the pressure in the reactor has reached the desired level, an initiator is introduced to start the polymerization reaction. The reaction temperature may vary depending on the characteristics of the initiator used, and those skilled in the art will know how to do it. Typically the temperature will be about 30°C to 150°C, preferably about 60°C to 120°C. Once the desired amount of polymer is reached in the reactor, the monomer feed will be stopped, but the initiator feed is optionally continued to consume residual monomers. The residual gas (containing unreacted monomers) is discharged and the latex is recovered from the reactor.
[0067] The surfactant used for polymerization can be any surfactant known in the art that can be used for PVDF emulsion polymerization, including perfluorinated, partially fluorinated and non-fluorinated surfactants. Preferably, the PVDF emulsion does not contain fluorinated surfactants, and no fluorinated surfactant is used in any part of the polymerization. The non-fluorinated surfactants that can be used for PVDF polymerization can be ionic and non-ionic in nature, including but not limited to 3-allyloxy-2-hydroxy-1-propanesulfonate, polyvinylphosphonic acid, polyacrylic acid, polyvinylsulfonic acid and its salts, polyethylene glycol and / or polypropylene glycol and its block copolymers, alkylphosphonates and siloxane-based surfactants.
[0068] The latex produced by the polymerization generally has a solid content of 10 to 60% by weight, preferably 10 to 50% by weight, and has a weight average particle size of less than 500 nm, preferably less than 400 nm, more preferably less than 300 nm. The weight average particle size is generally at least 20 nm, preferably at least 50 nm.
[0069] For use in the present invention, the latex is spray dried into a powder form and the powder is then granulated so that greater than 90% by weight, preferably greater than 95% by weight, of the agglomerated (granular) particles are 400 microns or greater but less than 2.5 mm, preferably 400 to 2000 microns, and have a bulk density greater than 0.4 g / cc, preferably greater than 0.6 g / cc. The granular particles have a raspberry form.
[0070] The polymer binder composition of the present invention is any thermoplastic polymer commonly used as an electrode binder. The polymer is typically a semi-crystalline polymer.
[0071] In some embodiments, the binder is a fluoropolymer composition and has a melting point above 100°C, preferably above 145°C, more preferably above 155°C.
[0072] The fluoropolymer composition used in the electrode composition preferably has a high molecular weight. As used herein, high molecular weight means a molecular weight of 100 % by weight at 450°F (232°C) and 100 seconds according to ASTM method D-3835. -1 A fluoropolymer (preferably PVDF) having a melt viscosity of greater than 10 kpoise, preferably greater than 15 kpoise, more preferably greater than 20 kpoise, and most preferably greater than 25 kpoise, as measured at room temperature.
[0073] Electrode slurry
[0074] The cathode forming slurry comprises a solvent, an electrode material (including a cathode active material and a conductive material) and a polymer binder. The anode forming slurry comprises a solvent, an electrode material (including an anode active material) and a polymer binder.
[0075] Solvents for slurries
[0076] Any suitable organic solvent of dissolved polymer adhesive can be used.Be used for dissolved polymer adhesive composition (preferably fluoropolymer, more preferably vinylidene fluoride polymer composition) to provide the organic solvent of adhesive solution according to the present invention can be preferably polar solvent, and its example can include: N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone, dimethyl formamide, N,N-dimethylacetamide, N,N-dimethyl sulfoxide, hexamethylphosphoramide, dioxane, tetrahydrofuran, tetramethylurea, triethyl phosphate and trimethyl phosphate.These solvents can be used alone or two or more are mixed and used.The granular polymer adhesive composition can be dissolved in a solvent to prepare a polymer adhesive solution.
[0077] Electrode Materials
[0078] The electrode forming composition can be obtained by adding and dispersing the electrode material (active material and optional additives, such as conductivity imparting additives) and the polymer binder according to the present invention and a solvent to provide an electrode forming slurry. The electrode material is preferably in a dry powdered form. Preferably, the particulate polymer binder composition is first dissolved in a solvent (providing a binder solution) and then the electrode material is added.
[0079] In the case of forming a positive electrode (cathode), the electrode material includes a cathode active material and a conductivity-imparting additive (conductive material). In the case of forming a negative electrode (anode), the electrode material includes a negative electrode active material, preferably a carbonaceous material.
[0080] In the case of forming a positive electrode (cathode), the cathode active material may include a composite metal sulfide represented by the general formula LiMY2, wherein M represents at least one transition metal, such as Co, Ni, Fe, Mn, Cr and V; and Y represents a sulfide element, such as O or S. Among them, a lithium-based composite metal oxide represented by the general formula LiMO2 is preferably used, wherein M is the same as above. Preferred examples thereof may include: LiCoO2, LiNiO2, LiNi x CO 1-x O2 and spinel structured LiMn2O4. Among them, Li-Co or Li-Ni binary composite metal oxides or Li-Ni-Co ternary composite metal oxides are particularly preferred from the perspective of high charge and discharge potential and excellent cycle characteristics, including LiNi x Co 1-x O2 (0≦×≦1). Cathode active materials include but are not limited to LiCoO2, LiNi 1-x Co x O2、Li 1-x Ni 1-y Co y O2, LiMO2 (M=Mn, Fe), Li[Nix Co 1-2x Mn x ]O、LiNi x Mn y Co z O2, LiM2O4 (M=Ti, V, Mn), LiM x Mn 2-x O4(M=Co 2+ 、Ni 2+ Mg 2+ , Cu 2+ 、Zn 2+ 、Al 3+ Cr 3+ ), LiFePO4, LiMPO4 (M = Mn, Co, Ni) and LiNi x CoyAlzO2. Preferred positive electrode materials include but are not limited to LiCoO2, LiNi x Co 1-x O2, LiMn2O4, LiNiO2, LiFePO4, LiNi x Co y Mn z O m 、LiNi x Mn y Al z O m , where x+y+z=1, m is an integer representing the number of oxygen atoms in the oxide to provide electron balance molecules; and lithium metal oxides, such as lithium cobalt oxide, lithium iron phosphate, lithium manganese phosphate, lithium nickel oxide and lithium manganese oxide.
[0081] In the case of forming a positive electrode (cathode), in order to improve the conductivity of the composite electrode layer formed by applying and drying the electrode forming composition of the present invention, a conductivity-imparting additive can be added. This conductivity-imparting additive can preferably be used in an amount of 0-10 weight parts or optional 0.1-10 weight parts per 100 weight parts of the active material constituting the positive electrode (cathode). Conductive agents include but are not limited to carbonaceous materials, such as graphite, graphite fine powder and fiber, carbon black, Ketjenblack, carbon fiber, carbon nanotubes and acetylene black, and fine powders and fibers of metals (such as nickel and aluminum). For conductive carbon black, preferably, the average particle size (diameter) measured by electron microscopy is 10-100nm.
[0082] In the case of forming a negative electrode (anode), the electrode material (active substance) may preferably contain a carbonaceous material such as graphite, activated carbon, or a carbonaceous material obtained by carbonizing a phenolic resin, and pitch.
[0083] The slurry may include other additives. Such additives are known to those skilled in the art. The adhesive composition of the present invention may optionally include 0 to 15 wt % based on the polymer, preferably 0.1 to 10 wt % of additives, including but not limited to thickeners, pH regulators, acids, rheological additives, anti-settling agents, surfactants, wetting agents, fillers, defoamers and fugitive adhesion promoters. Additional adhesion promoters may also be added to improve bonding properties and provide irreversible connectivity.
[0084] Forming electrodes
[0085] The slurry composition forming the positive electrode or the negative electrode can be used to form an electrode structure. More specifically, the slurry composition can be applied to at least one surface of a conductive substrate, preferably two surfaces, the conductive substrate comprising a metal foil or a metal mesh, the metal being, for example, iron, stainless steel, steel, copper, lithium, aluminum, nickel, silver or titanium, for small batteries, the thickness of the conductive substrate is, for example, 5-100 μm or 5-20 μm, and dried at, for example, 50-170° C. to form a composite electrode layer, for example, for small batteries, the thickness of the composite electrode layer is 10-1000 μm, preferably 10-200 μm, thereby providing an electrode structure for a non-aqueous battery.
[0086] The components of the slurry are mixed to form a uniform slurry. Example equipment for mixing the components includes, but is not limited to, a ball mill, a magnetic agitator, a planetary mixer, a high-speed mixer, a homogenizer, and a static mixer. Those skilled in the art can select sufficient equipment for this purpose. In order to obtain a polymer binder solution according to the present invention, it is preferred that about 0.1-20 parts by weight, particularly 1-15 parts by weight of the above-mentioned granular polymer binder composition is dissolved in 100 parts by weight of a solvent. If it is less than 0.1 parts by weight, the proportion of the polymer in the solvent is too small, and therefore it is easy to fail to show sufficient adhesive properties. If it exceeds 20 parts by weight, the viscosity of the resulting solution is easily too high, and therefore it is difficult to prepare a slurry composition for forming an electrode.
[0087] Preferably, the solid content (%) of the slurry is preferably in the range of 40 to 87 wt %, more preferably about 50 to 85 wt %.
[0088] The cathode formulation between active material, conductive agent and polymer binder can vary. Preferably, based on the total weight of the active material, conductive agent and polymer binder composition, the amount of active material is about 90-99 weight %; the amount of conductive agent is about 0.5 to 5 weight %, and the amount of polymer binder is about 0.5 to 5 weight %.
[0089] The formulation for the anode includes a conductive agent and a polymer binder. The amount of binder in the anode is about 0.5 to 5 weight percent based on the total weight of the anode active material and the polymer binder composition.
[0090] use
[0091] Electrodes formed by the methods of the present invention may be used to form electrochemical devices, including but not limited to batteries, capacitors, and other energy storage devices.
[0092] More specifically, the secondary battery basically includes a laminated structure including a positive electrode, a negative electrode and a separator disposed between the positive electrode and the negative electrode. The separator includes a fine porous membrane of a polymer material (e.g., PVDF, polyethylene or polypropylene) impregnated with an electrolytic solution. The non-aqueous electrolyte solution impregnated with the separator may include an electrolyte such as a solution of a lithium salt in a non-aqueous solvent (organic solvent). Examples of electrolytes may include: LiPF6, LiAsF6, LiClO4, LiBF4, CH3SO3Li, CF3SO3Li, LiN(SO2CF3)2, LiC(SO2CF3)3, LiCl and LiBr. Examples of organic solvents for such electrolytes may include: propylene carbonate, ethylene carbonate, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, γ-butyrolactone, methyl propionate, ethyl propionate, and mixtures thereof, but they are not exhaustive. Example
[0093] Test method:
[0094] The particle size of activated carbon was measured using a TYLER RX-29 sieve shaker.
[0095] Example:
[0096] Cathode slurry preparation: The cathode slurry formulation consists of an organic solvent such as N-methyl-2-pyrrolidone (NMP) or N-ethyl-2-pyrrolidone, at least one cathode active material, at least one conductive material, and a polymer binder composition.
[0097] A Dispermat [BYK-Gardner] was used for mixing on a laboratory scale.
[0098] Example 1. Li[Ni 0.6 Co 0.2 Mn 0.2 ]O2 / Super HSV900=96 / 2 / 2
[0099] Preparation of binder solution
[0100] for HSV900 (granular), more than 90% of the particles are between 400 microns and 2 mm.
[0101] for HSV900 (control), more than 90% by weight of the particles were between 5 and 30 microns.
[0102] 300 g NMP and 27 g PVDF were placed in a 500 mL stainless steel container. The container was first loaded with NMP, and then HSV900 (granular) or HSV900. Once mixing begins, it is easy to see the difference in mixing efficiency between granular powder and fine powder. The fine powder hardly soaks into the NMP as it forms a gel-like ball on the surface. In stark contrast, HSV900 (granular) shows excellent mixing performance as its bulk density is higher than the fine powder. Using a Dispermat (BYK Gardner) mixer, NMP and PVDF were mixed at 60°C for 1 hour. The solution was then allowed to cool. In order to check the dissolution efficiency, the solid content was checked. Solid content measurements were performed using a Mettler Toledo ME204. An aliquot of each solution was introduced into a 160°C oven for 1 hour.
[0103] Table 1. Solid content of 9 wt% PVDF in NMP solution
[0104]
[0105] Viscosity measurements were performed using a Brookfield viscometer at 25° C. A SSA7R chamber with a spindle number 15 was used.
[0106] Table 2. Solution viscosity of 9 wt% PVDF / NMP solution at 5.28 / sec.
[0107]
[0108] Preparation of cathode slurry
[0109] 10g Super P (conductive carbon black from TIMCAL) and 111g 9 wt% PVDF solution were loaded into a 500mL stainless steel container. Mixed for 1 minute at ambient conditions. 480g NMC622 was added to the container and mixed for 1 minute. Finally, the speed (rpm) was increased to obtain the desired slurry, the speed being between 2000rpm and 4000rpm. After 1 hour, the slurry viscosity, peeling and solid content of the obtained slurry were analyzed. Additional solvent was added to obtain the solid content.
[0110] Table 3. Solids content of cathode slurries made from corresponding Kynar(R) PVDF.
[0111]
[0112] Table 4. Viscosity of cathode slurry made of PVDF.
[0113]
[0114]
[0115] As shown in Table 4, the slurry viscosity gave unexpected results. Viscosity measurements were performed using a Brookfield viscometer at 25°C. An SSA7R chamber with a spindle number of 15 was used. Although HSV900 (granular) and The only difference between HSV900 is its bulk density, but the rheological behavior of the resulting slurries is quite different. This shows that the mixing efficiency in the solution preparation step affects the overall cathode slurry behavior.
[0116] Table 5. Cathodic disbonding data (arbitrary units).
[0117]
[0118] The slurry is then cast onto an aluminum foil current collector. The thickness can vary from 50 microns to 100 microns, more preferably 70 microns for laboratory testing. The coated current collector is placed in a 120°C oven for 30 minutes. Finally, the resulting cathode is compressed in a roller press. Cold pressing is performed. The compression ratio can be 20-30% (100um->70-80um).
[0119] To test 180 degree peeling, the cathode was cut into strips 1 inch wide and 15 cm long. Double-sided tape was applied to the substrate. The strip was then placed on one side of the tape to test the peeling. Finally, the peel tester records the load applied to separate the cathode from the tape. Here, only relative values are given, as the values themselves may vary depending on the peel tester supplier, current collector, and head speed of the peel tester. Interestingly, Kynar HSV900 (granular), which has better dissolution efficiency, showed higher peelability than Kynar HSV900.
[0120] Figures 1 to 3 show fluoropolymer powders. These figures show that the powder is an agglomerate of multiple individual primary particles that make up one powder particle. The average size of the powder particles in the figures is about 1 to 50 microns. Figures 4 to 6 show that the average size of the granular fluoropolymer is greater than 400 microns and is made of agglomerated primary particles. The SEM images show that the granulation process does not change the shape of the individual PVDF particles. The bulk density is increased by granulation.
Claims
1. A method for producing a battery electrode, the method comprising the following steps: a. providing a granular polymer adhesive composition, wherein the adhesive composition comprises agglomerated particles, wherein greater than 95% by weight of the agglomerated particles are 400 μm or greater but less than 2.5 mm, and a bulk density greater than 0.4 g / cc, b. mixing a particulate polymer binder composition, a solvent and an electrode material to provide an electrode-forming composition, wherein the polymer binder composition is dissolved in the solvent, c. applying an electrode-forming composition to at least one surface of a conductive substrate, and d. Evaporating the organic solvent in the electrode-forming composition to form a composite electrode layer on the conductive substrate.
2. The method of claim 1, wherein: The agglomerated particles have a raspberry morphology.
3. The method of claim 1, wherein: Step b includes: b1. adding the granular polymer binder composition to an organic solvent, b2. Mixing until dissolved to provide a solution of the granular binder, b3. Mixing the electrode material and the solution of the particulate binder to provide an electrode-forming composition.
4. The method of claim 1, wherein: The granular polymer binder composition comprises a polymer selected from the group consisting of fluoropolymers, SBR, ethylene vinyl acetate (EVA), acrylic polymers, polyurethanes, styrenic polymers, polyamides, polyesters, polycarbonates, and thermoplastic polyurethanes (TPUs), and combinations thereof.
5. The method of claim 1, wherein: The particulate polymer binder composition comprises a fluoropolymer.
6. The method of claim 3, wherein: The particulate polymer binder composition comprises a fluoropolymer.
7. The method of claim 5, wherein: According to ASTM method D-3835, at 450°F (232°C) and 100 seconds -1 The fluoropolymer has a melt viscosity greater than 5 kilopoise as measured at 100 rpm.
8. The method of claim 7, wherein: The fluoropolymer has a melt viscosity greater than 15 kilopoise.
9. The method of claim 5, wherein: The fluorine-containing polymer includes a polyvinylidene fluoride polymer comprising at least 50% by weight of vinylidene fluoride monomer units.
10. The method of claim 9, wherein: The fluorine-containing polymer includes a polyvinylidene fluoride polymer comprising at least 75% by weight of vinylidene fluoride monomer units.
11. The method of claim 5, wherein: The fluorine-containing polymer is a copolymer comprising vinylidene fluoride monomer units and 1 to 30 wt % of hexafluoropropylene monomer units.
12. The method according to any one of claims 1 to 11, wherein: The electrode material comprises an active material selected from the group consisting of oxides, sulfides or hydroxides of lithium and transition metals; carbonaceous materials; nano titanates and combinations thereof.
13. The method of claim 12, wherein: The electrode material also includes additives that impart conductivity.
14. The method according to any one of claims 1 to 11, wherein: The electrode material includes a carbonaceous material in the form of particles having an average diameter of 0.5-100 μm.
15. The method according to any one of claims 1 to 11, wherein: The agglomerated particles have a bulk density of 0.6 g / cc or greater.
16. The method according to any one of claims 1 to 11, wherein: The agglomerated particles are larger than 400 microns but smaller than 2000 microns.
17. An electrode formed by the method of any one of claims 1 to 16.
18. A battery comprising an electrode produced by the method of any one of claims 1 to 16.
Citation Information
Patent Citations
Process to polymerize vinylidene fluoride in an aqueous suspension
EP0120524A1
Vinylidene fluoride polymer-based binder solution and electrode-forming composition
US5776637A
Copolymers of vinylidene fluoride and hexafluoropropylene and process for preparing the same
US6187885B1
Binder solution and electrode-forming composition for non-aqueous-type battery
US6200703B1
Solvent-free electrode fabrication
CN106415892A